Biocompatibility studies on lanthanum oxide nanoparticles. Issue 4 (13th May 2015) - Brabu, B.; Haribabu, S.; Revathy, M.; Anitha, S.; Thangapandiyan, M.; Navaneethakrishnan, K. R.; Gopalakrishnan, C.; Murugan, S. S.; Kumaravel, T. S.
Graphical Abstract: Abstract: Lanthanum oxide nanoparticles (LONP), a rare earth metal oxide, have unique properties that make them a suitable candidate for several biomedical applications. We investigated certain key in vitro and in vivo biocompatibility endpoints on LONP. LONP were cytotoxic in in vitro assays and predominantly exerted their action via release of reactive oxygen species. These nanoparticles were neither irritants nor sensitizers in a rabbit model. LONP extracts did not exert any acute systemic toxicity effects in mice. On the other hand LONP exerted toxicity to the liver following oral administration, suggesting that these particles are absorbed from the gastrointestinal (GI) tract and deposited in the hepatobiliary system. LONP did not induce any mutation in the Ames test both in the presence or absence of S-9. These observations provide a base line biocompatibility and toxicity data on LONP. The current findings will also be useful in defining standards for nanoparticle containing devices.